THE COPING STRATEGY OF THE SEAWEED FARMING WORKERS IN RANDUSANGA VILLAGE, BREBES - Harmashinta Wahyu Arina; Gatot Sasongko; Yustinus Wahyudi (Faculty of Economics and Business, University of Pasundan, 2019)
The seaweed farming workers at Randusanga Wetan and Kulon village were facing a problem which also affecting their welfare, mainly their income. They could not decide their exact income because of their employment status, production and price instability. Coping strategy, which had been implemented, was one way to solve their problem as it made a connection and an active strategy. The form of ‘connection’ negotiated the portion of profit-sharing and enabled a household to borrow some money. Then, the active strategy was implemented by wild crab fishing, involving family member, intercropping with fish, working for 2-3 farmers, and utilizing ‘sumpil’. This way, they could achieve a good welfare while at the same time, kept producing for their income.